Two-dimensional axisymmetric formulation of high order spherical harmonics methods for radiative heat transfer. (May 2015) - Ge, Wenjun; Modest, Michael F.; Marquez, Ricardo
Abstract: The spherical harmonics ( P N ) method is a radiative transfer equation solver, which approximates the radiative intensity as a truncated series of spherical harmonics. For general 3-D configurations, N ( N + 1 ) / 2 intensity coefficients must be solved from a system of coupled second-order elliptic PDEs. In 2-D axisymmetric applications, the number of equations and intensity coefficients reduces to ( N + 1 ) 2 / 4 if the geometric relations of the intensity coefficients are taken into account. This paper presents the mathematical details for the transformation and its implementation on the OpenFOAM finite volume based CFD software platform. The transformation and implementation are applicable to any arbitrary axisymmetric geometry, but the examples to test the new formulation are based on a wedge grid, which is the most common axisymmetric geometry in CFD simulations, because OpenFOAM and most other platforms do not have true axisymmetric solvers. Two example problems for the new axisymmetric P N formulation are presented, and the results are verified with that of the general 3-D P N solver, a Photon Monte Carlo solver and exact solutions. Abstract : Highlights: Derivation of the axisymmetric formulation for the high order spherical harmonics methods. Derivation and application of Marshak׳s boundary conditions for axisymmetric PN. Matrix formulation of Marshak׳s boundary conditions for axisymmetric PN. Implementation of the axisymmetric PN on OpenFOAM. Calculating the radiative heat transfer for a real flame coupling PN with Full Spectrum Correlated-k(FSCK) model.